Rognoni and the fight against the Mafia (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The article reconstructs Virginio Rognoni’s contribution to the fight against the mafia during the dramatic five-year period (1978-1983) in which he was called to the office of Minister of the Interior considering also the fact that perhaps historiography has attributed to him a marginal role.
Keywords: antimafia, Vittorio Rognoni, memory, democracy, 416bis